Assistive technology for the visually impaired: How to provide independence and ease to meal preparation? - Serafimova, Ina Dimitrova (2022)
Disabilities are a reality many don’t think about too much unless one, or someone one knows, is affected by them. This work is motivated by this fact and is focused on attempting to improve the quality of life (QoL) of persons with visual impairment or blindness by facilitating the execution of one of the activities of daily living (ADL) – cooking independently. As this work will show, cooking with severe sight loss could prove easier or more difficult depending on various factors, the main one of which is time spent living with limited sight and, of course, proclivity for this activity. Easier, however, not easy. This is why the subject of this work is to provide a set of reliable, simple, and easy to use dispensers for oil and spices equipped with elements for identification of the various products. In order to, offer adequate results, this work began with contextualizing the target market by presenting statistics. This was followed by a glimpse of the reality of living with the limitations of visual impairment by examining the neural pathways that allow for multisensory processing (MP) and how that applies in the investigation and development of sensory substitution devices (SSD). Leaving the purely scientific and experimental part, this work proceeded to examining the evolution of assistive technology throughout the centuries and concluded by analyzing the current products on the market today. This analysis led to the compiling of plausible hypotheses for the solutions proposed by the author followed by final proposals and the development of proof-of-concept prototypes. The work concluded by presenting a business plan around the proposed products.